2012
DOI: 10.3390/s121217058
|View full text |Cite
|
Sign up to set email alerts
|

Improved Membrane-Based Sensor Network for Reliable Gas Monitoring in the Subsurface

Abstract: A conceptually improved sensor network to monitor the partial pressure of CO2 in different soil horizons was designed. Consisting of five membrane-based linear sensors (line-sensors) each with 10 m length, the set-up enables us to integrate over the locally fluctuating CO2 concentrations (typically lower 5%vol) up to the meter-scale gaining valuable concentration means with a repetition time of about 1 min. Preparatory tests in the laboratory resulted in a unexpected highly increased accuracy of better than 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 9 publications
(15 reference statements)
0
9
0
Order By: Relevance
“…The line sensor presented here covers the entire range of typical CO 2 concentrations in soil with high precision. This was demonstrated for <1.6% CO 2 by Lazik and Ebert (2012) and for concentrations <8% by Lazik and Sood (2016) for dry gases. In this study, we demonstrated the applicability of the line sensor for natural, humid soil conditions.…”
Section: Resultsmentioning
confidence: 73%
“…The line sensor presented here covers the entire range of typical CO 2 concentrations in soil with high precision. This was demonstrated for <1.6% CO 2 by Lazik and Ebert (2012) and for concentrations <8% by Lazik and Sood (2016) for dry gases. In this study, we demonstrated the applicability of the line sensor for natural, humid soil conditions.…”
Section: Resultsmentioning
confidence: 73%
“…Within these linearity ranges, such a membrane-based sensor can be calibrated by a gas-specific linear characteristic. To that end, the responses a1I have to be compared with reference gases of known composition [27,28,31,32]. …”
Section: Resultsmentioning
confidence: 99%
“…Insofar as different sensor arrangements cause different slopes, also the replacement of a selective membrane by a membrane of the same chemical formulation and geometry could cause a change in slope, e.g., due to changes in manufacturing. For instance, we report an experimentally determined value of about 21% vol s/mbar for CO 2 measurement with a tubular PDMS membrane of 10 m length, an inner radius of 0.7 mm and an outer radius of 1.8 mm [31]. In contrast, for a 40 m-long PDMS membrane with an inner radius 2 mm and outer radius of 3.5 mm, we determined a slope of about 190% vol s/mbar for the same range of 0–5% vol CO 2 that was added to air [32].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations